Differentially expressed miRNA profiles of serum derived extracellular vesicles from patients with acute ischemic stroke - Ghulam Jeelani Pir (13914063) (2024)
Background MicroRNAs (miRNAs) participate in diverse cellular changes following acute ischemic stroke (AIS). Circulating miRNAs, stabilized and delivered to target cells via extracellular vesicles (EVs), are potential biomarkers to facilitate diagnosis, prognosis, and therapeutic modulation. We aimed to identify distinctive expression patterns of circulating EV-miRNAs in AIS patients. Methods miRNA profiles from EVs, isolated from plasma samples collected within 24 h following AIS diagnosis, were examined between a dataset of 10 age-, gender- and existing comorbidities-matched subjects (5 AIS and 5 healthy controls, HC). We measured 2578 miRNAs and identified differentially expressed miRNAs between AIS and HC. An enrichment analysis was conducted to delineate the networks and biological pathways implicated by differentially expressed microRNAs. An enrichment analysis was conducted to delineate the networks and biological pathways implicated by differentially expressed microRNAs. Results Five miRNAs were differentially expressed between stroke (AIS) versus control (HC). hsa-let-7b-5p, hsa-miR-16-5p, and hsa-miR-320c were upregulated, whereas hsa-miR-548a-3p and hsa-miR-6808-3p, with no previously reported changes in stroke were downregulated. The target genes of these miRNAs affect various cellular pathways including, RNA transport, autophagy, cell cycle progression, cellular senescence, and signaling pathways like mTOR, PI3K-Akt, and p53. Key hub genes within these networks include TP53, BCL2, Akt, CCND1, and NF-κB. These pathways are crucial for cellular function and stress response, and their dysregulation can have significant implications for the disease processes. Conclusion Our findings reveal distinct circulating EV-miRNA expression patterns in AIS patients from Qatar, highlighting potential biomarkers that could aid in stroke diagnosis and therapeutic strategies. The identified miRNAs are involved in critical cellular pathways, offering novel insights into the molecular mechanisms underlying stroke pathology. Circulating EV-miRNAs differentially expressed in AIS may have a pathophysiological role and may guide further research to elucidate their precise mechanisms. Other Information Published in: Brain Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.brainres.2024.149171